Classifications of Translation Surfaces in Isotropic Geometry with Constant Curvature - Aydin, M. E. (Springer, 2020)
We classify translation surfaces in isotropic geometry with arbitrary constant isotropic Gaussian and mean curvatures under the condition that at least one translating curve lies in the plane.
Keywords: Hypersurfaces; Spaces